IMPLEMENTASI NILAI-NILAI MULTIKULTURAL UNTUK MEMPERBAIKI PERILAKU SANTRI - Syaiful Anwar (QATHRUNÂ, 2021)
This study aims to 1) determine the multicultural values planting model in Daar El Qolam Islamic Boarding School. 2) knowing the implementation of multicultural values found in Daar El Qolam Islamic Boarding School. 3) knowing the impact of planting and implementing multicultural values on the personality of students in the El Qolam Daar Islamic Boarding School. This type of research is descriptive with a qualitative approach. While the sources of research are leaders, Islamic boarding schools, head of care, head of worship, principals, teachers / teachers and students. Data collection techniques are done through interviews and observation and documentation. Data analysis techniques were performed using data collection, data reduction, data presentation and data inference. The findings in this study are the values of multicultural education found in Islamic Boarding Schools da el-Qolam are exemplary methods and methods of habituation. The impact of the cultivation of multicultural education is the growth of mutual tolerance, respect and acceptance of others, mutual cooperation is not hostile and not mutual there are conflicts due to differences in culture, ethnicity, language, customs. Hopefully this research is useful for Daar el-Qolam Islamic boarding school in particular and also beneficial for other educational institutions so that multicultural education can be implemented properly and correctly.